Memórias e experiências para além da exposição: (re)visitar o passado no Museu do Aljube - Joana Miguel Almeida (Midas: Museus e Estudos Interdisciplinares)
This paper is the result of ethnographic research carried out in the Aljube Museum – Resistance and Freedom (Lisbon). At the time of its opening (2015), the Aljube Museum was unprecedented in the Portuguese museological context. The research sought to understand the meanings woven by those who motivate processes of patrimonialization of places like the Aljube, those who experienced them during the dictatorship, and those who visit them today, in democracy. Methodologically, I privileged the use of participant observation, including 30 guided tours and a set of semi-structured interviews with visitors. This article focuses specifically on how, beyond its exhibition, the Aljube Museum can be seen as a space for evoking memories and subjectivities, not only for former political prisoners and those who resisted the dictatorship, but also for those who visit it and find a space for sharing, and even searching for their personal and familial memories, as well as their understandings of the past and how we engage with it in the present.